Analysis of Youth Pastoral Care in Croatia Through the Lens of the Synod on Youth - Blaženka Valentina Mandarić (Religions)
Youth pastoral care is a part of the Church’s pastoral mission directed towards men and women who can be categorised as young people. Young people were the central theme of the 15th Ordinary General Assembly of the Synod of Bishops, held in Rome from 3 to 28 October 2018, under the motto Young People, the Faith, and Vocational Discernment. Based on an analysis of the preparatory and final documents of the Synod—particularly the Preparatory Document, Instrumentum Laboris, Final Document, Christus Vivit—as well as relevant scientific analyses and interpretations, we have identified the most significant societal challenges facing the youth, along with the key guidelines and recommendations of the Synod for working with them. The motivation for writing this article arises from the fact that the Synod on Youth, which took place in Rome from 3 to 28 October 2018, under the theme “Youth, Faith, and Vocational Discernment,” did not generate significant interest within the Church in Croatia. This is evidenced by several indicators: the responses of young people to the questionnaire sent to all bishops’ conferences were never published; there has been a lack of relevant commentary, articles, or academic studies on the Synod; and among the many pre- and post-synodal documents, only “Christus vivit” has been translated into Croatian. Given that youth ministry plays an important role in the pastoral activities of the Church in Croatia, we sought to explore whether, and to what extent, the core recommendations of the Synod on Youth continue to be reflected in current pastoral work with young people in the country. Our approach involved analysing the pre- and post-synodal documents from the Synod on Youth to identify key recommendations for youth ministry. We then examined the current youth pastoral programs in seven (arch)dioceses, as well as the pastoral plans of the Youth Office of the Croatian Bishops’ Conference, through the lens of the Synod’s main recommendations. Analytical, descriptive, and critical methods were used in the research. The analysis of the aforementioned youth pastoral programs confirmed that the most important guidelines and recommendations of the Synod, although some only partially, are integrated into youth pastoral care in Croatia.